Using multivariate data analysis to project performance in biathletes and cross-country skiers - Jones, T. W.; Lindblom, H. P.; Laaksonen, M. S.; McGawley, K. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To determine whether competitive performance, as defined by International Biathlon Union (IBU) and International Ski Federation (FIS) points in biathlon and cross-country (XC) skiing, respectively, can be projected using a combination of anthropometric and physiological metrics. Shooting accuracy was also included in the biathlon models.